2013
DOI: 10.1007/s10165-013-0848-5
|View full text |Cite
|
Sign up to set email alerts
|

MEFV gene variations in patients with systemic lupus erythematosus

Abstract: OBJECTIVE: The aim of this study was to investigate the frequency of familial Mediterranean fever (FMF)-associated MEFV gene variations in patients with systemic lupus erythematosus (SLE). METHODS: The study group comprised 190 SLE patients and 101 healthy controls of Turkish origin with no clinical features of FMF. All individuals were genotyped for the four most common MEFV gene variations (M694V, M680I, V726A and E148Q) by PCR-restriction fragment len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…13,14 Recently, a negative association (absence of SLE in large cohorts of FMF patients) and a somewhat protective effect of MEFV mutations on renal morbidity have been reported. 15,16 Similarly, Ozen et al observed the absence of SLE among FMF patients and vice versa in a pediatric cohort and proposed that high levels of CRP may play a protective role against the development of SLE in FMF patients. 17 Dysfunctional innate and/or adaptive immune responses to external pathogens or endogenous molecules derived from a ''stressed host'' account for several human diseases, and increasing scientific information on the role of innate immunity in SLE pathogenesis -such as the role of the PYRIN domain in activating the inflammasomes -makes the possible effect of FMF on SLE severity rather interesting.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…13,14 Recently, a negative association (absence of SLE in large cohorts of FMF patients) and a somewhat protective effect of MEFV mutations on renal morbidity have been reported. 15,16 Similarly, Ozen et al observed the absence of SLE among FMF patients and vice versa in a pediatric cohort and proposed that high levels of CRP may play a protective role against the development of SLE in FMF patients. 17 Dysfunctional innate and/or adaptive immune responses to external pathogens or endogenous molecules derived from a ''stressed host'' account for several human diseases, and increasing scientific information on the role of innate immunity in SLE pathogenesis -such as the role of the PYRIN domain in activating the inflammasomes -makes the possible effect of FMF on SLE severity rather interesting.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, a negative association (absence of SLE in large cohorts of FMF patients) and a somewhat protective effect of MEFV mutations on renal morbidity have been reported. 15,16 Similarly, Ozen et al. observed the absence of SLE among FMF patients and vice versa in a pediatric cohort and proposed that high levels of CRP may play a protective role against the development of SLE in FMF patients.…”
Section: Introductionmentioning
confidence: 96%
“…17 The presence of the MEFV mutation in SLE patients may modify the phenotype of the disease 18 by enhancing inflammatory episodes and attenuating renal manifestations. 6 For example, the frequency of variants in the MEFV mutation (M694V, M680I, V726A and E148Q) in Turkish Juvenile SLE and adults SLE patients was 22.7% 19 and 15% 20 respectively. This frequency is high as that reported in healthy Turkish population, which was found to range between 10–20%.…”
Section: Discussionmentioning
confidence: 99%
“…Both FMF and heterozygote carriage of MEFV variants have been associated with a more frequent occurrence of vasculitic syndromes particularly HenochSchönlein purpura and to a lesser extent polyarteritis nodosa and perhaps Behçet's syndrome [ 75 , 76 ] although no association has been shown with systemic lupus erythematosus [ 77 ]. A link between FMF and Henoch-Schönlein purpura (HSP) has been recognized for more than 30 years [ 78 ] and may predispose to more severe HSP with a higher risk of complications [ 79 , 80 ].…”
Section: Vasculitismentioning
confidence: 99%